Acceleration and focusing of electron bunches by wakefields in plasma produced in neutral gas by a nonresonant sequence of bunches - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I. (Вопросы атомной науки и техники, 2012)
It is experimentally investigated the possibility of accelerating and focusing of relativistic electron bunches by wakefields excited by their sequence in plasma, produced during its passage through the neutral gas, caused by the displacement of bunches into corresponding phases of excited field in the presence of mismatch between the bunch repetition frequency and plasma frequency. The mismatch is achieved by changing the pressure of the neutral gas at a fixed beam current density. Energy loss of some bunches and energy gain of others in the presence of other mismatch are estimated from the energy spectrum obtained from the imprints on the glass plate of bunches deflected with the transverse magnetic field. Focusing/defocusing of electron bunches is demonstrated by the change of the transverse sizes of imprints of nondeflected bunches and corresponding temporal modulation of the axial current density of the beam measured by Faraday cup of small cross-section